Ritual Embodied Historiography: Foundational Theory on the Reconstruction of Classical Han Dynasty Chinese Dance - Jie, Cui; Saearani, Muhammad Fazli Taib (Gema Cendekia Institute, 2025)
The reconstruction of ancient Chinese dance, particularly from the Han Dynasty period, faces epistemological, material, and cultural challenges due to the scarcity of archives and the fragmentation of visual and textual sources. This study analyses three contemporary reconstruction works—Tonque Ji (Sun Ying), Han Painting Dance Experimental Performance (Liu Jian), and the Yong Dance Series (Tian Tian)—employing a grounded theory approach to map conceptual patterns in dance reconstruction practices. The findings propose the conceptual model of Ritual Embodied Historiography (REH), which frames reconstruction as an embodied historiographical process, wherein the body functions as a living archive, an affective medium, and a site of symbolic reactivation through engagement with material artefacts and contemporary sociocultural contexts. The study indicates that Han dance reconstruction cannot be fully understood through conventional Western frameworks but requires approaches grounded in cosmology, Confucian ritualism, and Eastern epistemology. The model extends global dance reconstruction scholarship by emphasising the body’s role as an agent of historical knowledge production in performance practice.